Factors Affecting Quality of Life in Hemodialysis Patients - Yonata A; Islamy N; Taruna A; Pura L (International Journal of General Medicine, 2022)
Ade Yonata,1 Nurul Islamy,2 Ahmad Taruna,1 Lukman Pura1 1Department of Internal Medicine, Faculty of Medicine, Lampung University–Abdul Moelok Hospital, Lampung, Indonesia; 2Department of Obstetry Ginecology, Faculty of Medicine, Lampung University–Abdul Moelok Hospital, Lampung, IndonesiaCorrespondence: Ade Yonata, Department of Internal Medicine, Faculty of Medicine, Lampung University, Jl. Prof. Soemantri Brojonegoro No. 1, Bandar Lampung, 35145, Indonesia, Tel/Fax +62721 7691197, Email adeyumi@gmail.comBackground: Hemodialysis is one of the main therapies for patients with end-stage renal disease. Quality of life is essential in the management of chronic kidney disease (CKD) patients undergoing hemodialysis. Factors that influence the quality of life in hemodialysis patients must be identified.Purpose: This research evaluated the quality of life in CKD patients undergoing hemodialysis and determined factors affecting the quality of life.Patients and Methods: This study used an analytical survey method with a cross-sectional design. The Subjective Global Assessment (SGA) questionnaire was used to evaluate nutritional status, and the KDQOL-SFTM questionnaire was used to evaluate quality of life. The bivariate statistical test applied was the Student’s t-test or the Mann–Whitney U-test. Multivariate analysis was done using logistic regression.Results: The total number of hemodialysis patients in the study was 124. Their median age was 44 years. The patients consisted of 66 (53%) men and 58 (47%) women. Overall, 84 patients had good quality of life (67.7%), and 40 (32.3%) reported poor quality of life. Our study showed a relationship between economic status and quality of life (p = 0.029) and between the number of comorbid factors and quality of life (p = 0.014). No relationship was found between nutritional status and quality of life (p = 0.121). Multivariate analysis using logistic regression analysis showed that the number of comorbidities was a significant factor in quality of life (p = 0.004, OR = 3.4 [1.67– 7.46]).Conclusion: The majority of hemodialysis patients had good quality of life. Logistic regression analysis found that the number of comorbidities was a significant factor in the quality of life of hemodialysis patients. Comorbidities in hemodialysis patients must be managed to improve their quality of life.Keywords: comorbid, quality of life, hemodialysis